Sexual Gratification as an Expanded Form of Corruption Crime Under Indonesian Positive Law - Hutagalung, Jantarda Mauli; Saputri, Adhalia Septia (Green Publisher Indonesia, 2024)
Along with its development, the category of sexual gratification emerged which received a lot of attention from the public and law enforcement officials. This sexual satisfaction is different from the satisfaction we know in general. The difference lies in the object. Sexual gratification is a form of degrading women's dignity. In Indonesia, sexual gratification has not been explicitly regulated. Therefore, this research will discuss the regulation of sexual gratification based on positive law in Indonesia and the evidence. From the results of the analysis it is known that sexual gratification can be included in the provisions of Article 12 B paragraph 1 of Law 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes. This can be found in the phrase